Pengaruh Diversifikasi terhadap Kinerja Perusahaan - Rafrini Amyulianthy; Nuraini Sari (Bina Nusantara University, 2013)
For many years, the benefit and cost of corporate diversification strategy have been debatable. This research provides empirical evidence on corporate diversification and its consequences toward firm value. Corporate diversification as part of internal market mechanism can have benefit and cost on performance of the firm. The writers estimated that diversification strategy would reduce firm value especially in situation like Indonesia with less developed financial market and many companies are still suffering from monetary crises in recent years. The writers found that companies with diversified business segment have negative excess value comparing with stand alone firms. In relation with firms characteristics, it shows that tobins q and asset size positively related with firm value. This result rejects internal capital market hypothesis.